Impact of acquisitions on firms' performance - Marianna Endresz; Péter Gábriel (Magyar Nemzeti Bank, 2024)
This paper estimates the impact of acquisitions on various firm-level performance measures of Hungarian firms. Using difference-in-differences estimation with matching, we show that the performance of the acquirer improves significantly following an acquisition. By controlling for the - typically weaker - efficiency of the target, we also estimate the overall efficiency gain. Our results indicate that acquisitions are powerful tools to improve efficiency in the Hungarian economy. The estimated impacts are heterogeneous. Efficiency gains are higher if the acquirer is smaller and less efficient prior to the acquisition, highlighting that improving scale efficiency is an important motive for acquisitions. Furthermore, if the acquirer and target companies had business links beforehand, the productivity gain is twice as large. Acquisitions made during recessions are also different in some ways. Firms make fewer acquisitions, although the number of potential target companies increases. Because acquirers become more selective, the efficiency gains remain sizeable even in the unfavourable business environment.
Keywords: C22; D22; D24; 330; mergers; acquisitions; efficiency; productivity; matching